A geochemical investigation of the free and carbonate-bound organic matter in the clay-sized fraction of argillaceous source rocks and its significance for biogenic interpretation - Yue Zhao (KeAi Communications Co., Ltd., 2018)
Abstract The molecular composition and biomarker distribution of various occurrences of organic matter in argillaceous source rocks developed in fresh and saline lacustrine environments were revealed by successive treatments of solvent extraction followed by acid hydrolysis using gas chromatography–mass spectrometry. The free fraction obtained by solvent extraction provided abundant geochemical information concerning the sedimentary environment, thermal maturity and biogenic origin, and obvious differences existed between fresh and saline lacustrine source rock samples. Our research results indicate that the carbonate-mineral-bound (CM-bound) fraction released by successive acid hydrolysis could also serve as a significant biogenic indicator, as the bicyclic sesquiterpenoids, indicative of Botryococcus braunii origin, were specifically detected in quite high abundance in the acid-soluble fraction. In addition, the light end hydrocarbons were much better preserved in the acid-soluble fraction, and elemental sulfur was only detected in the CM-bound fraction, suggesting a relatively confined environment for the CM-bound fraction, which thus could preserve additional geochemical information compared to that of the free fraction. The CM-bound fraction also exhibited discernable differences between fresh and saline lacustrine samples. Therefore, it can be concluded that comprehensive analysis of free and CM-bound fractions in the argillaceous source rocks can provide a more authentic and objective interpretation of geologic conditions.